Influence mechanism of the diameter of the energy accumulation hole on the bi-directional cumulative tension blasting - Zhang, Xiaohu; Jiang, Yijun; Zhao, Peng; Zhao, Zhifeng; Hao, Xiaobo (Frontiers in Earth Science, 2024)
This study focuses on evaluating the influence of the energy accumulation hole diameter on bi-directional cumulative tension blasting. Firstly, the penetration depth of bi-directional cumulative tension blasting is determined, followed by an analysis of the corresponding fracture mechanics behavior. Secondly, the Smooth Particle Hydrodynamics (SPH) method is used for numerical analysis of the bi-directional cumulative tension blasting process, and the Johnson-Holmquist constitutive model is then employed to examine the dynamic process during tensile blasting-induced cracking. This analysis provides insights into damage development, particle distribution, stress distribution, and crack propagation in the rock at different opening diameters. The findings reveal that, except for the 2 mm case, bi-directional cumulative tension blasting effectively produces directional cracks aligned with the energy accumulation direction. For hole diameters between 4-8 mm, linear through cracks form in the energy accumulation direction. However, a 2 mm diameter opening only generates short shear cracks around the blast hole.With energy accumulation hole diameters ranging from 10-14 mm, the crack propagation depth is insufficient for complete penetration, despite the presence of linear cracks in the energy accumulation direction. When diameter exceeds 14 mm, symmetrical airfoil cracks appear in non-concentrated energy directions, with larger diameters resulting in shorter crack propagation lengths. During the directional cracking process for hole diameters of 4-8 mm, explosive particles facilitate crack expansion in width and length through the action of a "gas wedge". On-site blasting tests confirm the excellent directional pre-splitting effect of bi-directional cumulative tension blasting.